2008
DOI: 10.4049/jimmunol.180.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Rapamycin Generates Apoptosis-Resistant Donor Th2 Cells That Persist In Vivo and Prevent Hemopoietic Stem Cell Graft Rejection

Abstract: Because ex vivo rapamycin generates murine Th2 cells that prevent Graft-versus-host disease more potently than control Th2 cells, we hypothesized that rapamycin would generate Th2/Tc2 cells (Th2/Tc2.R cells) that abrogate fully MHC-disparate hemopoietic stem cell rejection more effectively than control Th2/Tc2 cells. In a B6-into-BALB/c graft rejection model, donor Th2/Tc2.R cells were indeed enriched in their capacity to prevent rejection; importantly, highly purified CD4+ Th2.R cells were also highly efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
30
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 67 publications
(56 reference statements)
7
30
1
Order By: Relevance
“…SLR can also alter the polarization signals required for effector T cell differentiation. For instance, SLR has been reported to promote Th2-type polarization in vitro and both Th2 and Tc2 graftprotecting lymphocytes in an in vivo graft versus host disease (GVHD) model (44). Other studies have documented a critical role of mTOR in the generation of memory CD8+ T cells (25) and in the regulation of dendritic cell maturation (8,11,45).…”
Section: Discussionmentioning
confidence: 99%
“…SLR can also alter the polarization signals required for effector T cell differentiation. For instance, SLR has been reported to promote Th2-type polarization in vitro and both Th2 and Tc2 graftprotecting lymphocytes in an in vivo graft versus host disease (GVHD) model (44). Other studies have documented a critical role of mTOR in the generation of memory CD8+ T cells (25) and in the regulation of dendritic cell maturation (8,11,45).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described that mTOR inhibition by rapamycin treatment during the expansion and contraction phases improved both the quality and quantity of memory T cells after primary immunization in preclinical models (14)(15)(16)(17). Rapamycin seems to prolong the survival of Ag-specific T cells (18,19). It paradoxically enhances the Ag-specific CD8 + T cell response and accelerates memory T cell formation in vivo (15).…”
mentioning
confidence: 99%
“…1 These results, combined with our findings using ex vivo rapamycin in murine allogeneic transplantation models, 2,3 indicate that postautophagy "T-Rapa" cells represent a particularly potent cell population for mediation of transplantation responses; indeed, in a phase II clinical trial we have shown that allogeneic donor T-Rapa cells are safely administered in the setting of lowintensity hematopoietic cell transplantation and mediate a potentially favorable balance of pro-engraftment, graft-vs. -tumor, and graft-vs. -host disease (GVHD) effects. 4 As such, as we have recently reviewed, 5 it is possible to 'harness' autophagy for the enhancement of T cell therapy.…”
Section: Introductionmentioning
confidence: 67%
“…We and others have showed that ex vivo T cells cultured in the presence of rapamycin are more robust T cell phenotype due in part to their high expression of antiapoptotic molecules such as BCL2L1. 1,3,39 Of note, the DTYMKΔ-AZT axis executes an apoptotic cascade through disruption of the mitochondrial inner membrane and activation of caspase 3, thereby resulting in apoptosis. 19 Because of this potential mechanistic antagonism (favorable mitochondrial function of T-Rapa cells; mitochondrial action of DTYMKΔ-AZT axis), we reasoned that the T-Rapa cells would represent a stringent population for testing the capability of the DTYMKΔ-AZT cell-fate control axis to eliminate potentially resistant T cell populations.…”
Section: Discussionmentioning
confidence: 99%